18.9% Efficient Organic Solar Cells Based on n‐Doped Bulk‐Heterojunction and Halogen‐Substituted Self‐Assembled Monolayers as Hole Extracting Interlayers. Issue 45 (3rd October 2022) - Lin, Yuanbao; Zhang, Yadong; Zhang, Junxiang; Marcinskas, Mantas; Malinauskas, Tadas; Magomedov, Artiom; Nugraha, Mohamad Insan; Kaltsas, Dimitris; Naphade, Dipti R.; Harrison, George T.; El‐Labban, Abdulrahman; Barlow, Stephen; et al.
Abstract: The influence of halogen substitutions (F, Cl, Br, and I) on the energy levels of the self‐assembled hole‐extracting molecule [2‐(9 H ‐Carbazol‐9‐yl)ethyl]phosphonic acid (2PACz), is investigated. It is found that the formation of self‐assembled monolayers (SAMs) of [2‐(3, 6‐Difluoro‐9 H ‐carbazol‐9‐yl)ethyl]phosphonic acid (F‐2PACz), [2‐(3, 6‐Dichloro‐9 H ‐carbazol‐9‐yl)ethyl]phosphonic acid (Cl‐2PACz), [2‐(3, 6‐Dibromo‐9 H ‐carbazol‐9‐yl)ethyl]phosphonic acid (Br‐2PACz), and [2‐(3, 6‐Diiodo‐9 H ‐carbazol‐9‐yl)ethyl]phosphonic acid (I‐2PACz) directly on indium tin oxide (ITO) increases its work function from 4.73 eV to 5.68, 5.77, 5.82, and 5.73 eV, respectively. Combining these ITO/SAM electrodes with the ternary bulk‐heterojunction (BHJ) system PM6:PM7‐Si:BTP‐eC9 yields organic photovoltaic (OPV) cells with power conversion efficiency (PCE) in the range of 17.7%–18.5%. OPVs featuring Cl‐2PACz SAMs yield the highest PCE of 18.5%, compared to cells with F‐2PACz (17.7%), Br‐2PACz (18.0%), or I‐2PACz (18.2%). Data analysis reveals that the enhanced performance of Cl‐2PACz‐based OPVs relates to the increased hole mobility, decreased interface resistance, reduced carrier recombination, and longer carrier lifetime. Furthermore, OPVs featuring Cl‐2PACz show enhanced stability under continuous illumination compared to ITO/PEDOT:PSS‐based cells. Remarkably, the introduction of the n‐dopant benzyl viologen into the BHJ further boosted the PCE of the ITO/Cl‐2PACz cells to a maximum value of 18.9%, a record‐breaking value for SAM‐based OPVs and on par with the best‐performing OPVs reported to date. Abstract : The conventional hole‐extracting polymer poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate in organic bulk‐heterojunction (BHJ) photovoltaics is replaced with engineered self‐assembled monolayers (SAMs). Combining the nanometre‐thin SAM interlayers with an n‐doped BHJ, organic photovoltaics with improved stability and a maximum power conversion efficiency of 18.9% are demonstrated.